Association of the preoperative neutrophil-to-lymphocyte and platelet-to-lymphocyte ratios with lymph node metastasis and recurrence in patients with medullary thyroid carcinoma. Issue 40 (October 2016) - Jiang, Ke; Lei, Jianyong; Chen, Wenjie; Gong, Yanping; Luo, Han; Li, Zhihui; Gong, Rixiang; Zhu, Jingqiang
Abstract : Abstract: The preoperative neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are known to be prognostic factors in several cancers. However, no previous investigation has been performed to evaluate the significance of the NLR and PLR in medullary thyroid carcinoma (MTC). The aim of this study was to identify the ability of the preoperative NLR or PLR to predict lymph node metastasis and recurrence in patients with MTC. Data from all patients with MTC who had undergone surgery at our institution from May 2009 to May 2016 were retrospectively evaluated. Receiver operating characteristic (ROC) analysis was performed to identify optimal NLR and PLR cutoff points, and we assessed independent predictors of lymph node metastasis and recurrence using univariate and multivariate analyses. Based on the inclusion and exclusion criteria, a total of 70 patients were enrolled in this study. The ideal cutoff points for predicting lymph node involvement were 2.7 for the NLR and 105.3 for the PLR. The optimal cutoff points of the NLR and PLR for predicting recurrence were 2.8 and 129.8, respectively. Using the cutoff values, we found that PLR>105.3 (odds ratio [OR] 4.782, 95% confidence interval [CI] 1.4–16.7) was an independent predictor of lymph node metastasis and that PLR>129.8 (OR 3.838, 95% CI 1.1–13.5) was an independent predictor of recurrence. Our study suggests that the preoperative PLR, but not NLR, was significantly associated with lymph node metastasis and recurrence in patients with MTC.